PWE-034 The incidence of post-operative respiratory complications following colon surgery in an eras population. (17th June 2017) - Hancock, C; McIlveen, E; Porteous, J; Moug, S
Abstract : Introduction: Abdominal surgery is associated with reduced diaphragmatic function post-operatively leading to an increased risk of respiratory complications, ranging from lower respiratory tract infections (LRTI) to respiratory distress, hypoxia and ITU admission. We aimed to determine the incidence of respiratory complications in patients undergoing elective colorectal surgery. Method: Data was collected from the ERAS (Enhanced Recovery after Surgery) database and included patients who had undergone colorectal surgery within a 12 month period from August 2015 to July 2016. This included patient demographics, co-morbidities (including BMI and ASA grade), surgery performed, length of hospital stay, post-operative complications, length of level 2/3 stay and details of patient readmissions. In addition baseline oxygen saturations, pre-operative haemoglobin and creatinine levels were recorded. Data was analysed to determine the incidence of post-operative respiratory complications and any influencing variables. Results: There were 101 consecutive patients; mean age 60.8 (21–89), 51.5% male. The most common types of surgery were open right hemicolectomy (18.4% (19)) and reversal of ileostomy (16.5% (17)). The mean length of total hospital admission was 7.9 days. Post-operatively, 3.0% (n=3) patients required increased respiratory support; 2.0% (n=2) of which received high flow nasal oxygen within 4 hours following surgery and 1.0% (n=1) received CPAP due to hypoxia and type 2 respiratory failure. 1.0% (n=1) required admission to ITU. The overall respiratory complication rate was 6.9% (n=7): 5.9% LRTI; 0.99% pleural effusion; 0.99% type 2 respiratory failure; 0.99% influenza A. Of the patients who developed respiratory complications, 50% of them had a previous history of asthma, and 100% of them were at least ASA class II. Their hospital stay was significantly longer than non-respiratory complication patients (mean 12.8 days versus 7.9 days, p<0.001 (CI 2.62–8.74)). There was no significant association with any other pre-operative patient variables. On comparison, non-respiratory complications were much less, such as acute kidney injury (3.0%, n=3) and superficial surgical infection (3.0%, n=3). Conclusion: Respiratory complications are one of the commonest post-operative complications following elective colorectal surgery, resulting in a longer duration of hospital admission. This suggests that there is a role for an improvement strategy and the PRISM (Prevention of respiratory insufficiency after surgical management) trial will determine whether the rates of respiratory complications can be reduced by providing CPAP routinely in the post-operative period. Disclosure of Interest: None Declared